B‐cell anergy induces a Th17 shift in a novel B lymphocyte transgenic NOD mouse model, the 116C‐NOD mouse. Issue 3 (12th January 2016) - Carrascal, Jorge; Carrillo, Jorge; Arpa, Berta; Egia‐Mendikute, Leire; Rosell‐Mases, Estela; Pujol‐Autonell, Irma; Planas, Raquel; Mora, Conchi; Mauricio, Dídac; Ampudia, Rosa Maria; Vives‐Pi, Marta; Verdaguer, Joan
Abstract : The 116C‐NOD is a β‐cell autoreactive B lymphocyte transgenic mouse model. Type 1 Diabetes incidence is decreased in 116C‐NOD compared with NOD mice. Whereas 116C B lymphocytes display an anergic phenotype, 116C T lymphocytes are fully functional and develop a predominant Th17 response following B lymphocyte interaction. Abstract : Autoreactive B lymphocytes play a key role as APCs in diaebetogenesis. However, it remains unclear whether B‐cell tolerance is compromised in NOD mice. Here, we describe a new B lymphocyte transgenic NOD mouse model, the 116C‐NOD mouse, where the transgenes derive from an islet‐infiltrating B lymphocyte of a (8.3‐NODxNOR) F1 mouse. The 116C‐NOD mouse produces clonal B lymphocytes with pancreatic islet beta cell specificity. The incidence of T1D in 116C‐NOD mice is decreased in both genders when compared with NOD mice. Moreover, several immune selection mechanisms (including clonal deletion and anergy) acting on the development, phenotype, and function of autoreactive B lymphocytes during T1D development have been identified in the 116C‐NOD mouse. Surprisingly, a more accurate analysis revealed that, despite their anergic phenotype, 116C B cells express some costimulatory molecules after activation, and induce a T‐cell shift toward a Th17 phenotype. Furthermore, this shift on T lymphocytes seems to occur not only when both T and B cells contact, but also when helper T (Th) lineage is established. The 116C‐NOD mouse model could be useful to elucidate the mechanisms involved in the generation of Th‐cell lineages.